Betamethasone administration as a treatment of choice in local post-tattoo complications - O. N. Karymov; A. A. Vorobyov; S. A. Kalashnikova; L. V. Polyakova; M. N. Vyskub (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
The aim of the study is to determine the effectiveness of betamethasone in the treatment of local post-tattoo complications, depending on the mode of administration.Materials and methods. The work was carried out on 90 male rats which had been tattooed (n = 30 - a negative control group; n = 30 - a comparison group: a subcutaneous administration of 1 ml of a betamethasone solution; n = 30 - an experimental group: an administration of 1 ml of a betamethasone solution using a tattoo machine), 15 - intact rats. Withdrawal from the experiment took place on the 3rd, 10 th and 21st days. The skin samples were fixed in 10% formalin, followed by histological posting and manufacturing of micropreparations, then staining with hematoxylin and eosin, according to Van Gieson. A morphometric study included determination of the volume fraction (VF) of the epidermis; dermal fibers; pigment; inflammatory cells; macrophages (%), as well as the pigment depth (μm) and the severity of edema.Results. The study found out that in the process of the betamethasone administration using a tattoo machine, the drug was uniformly administrated over the entire area of the tattoo; hereby, the phenomena of edema and inflammatory infiltration were insignificant. The dermal fibers were located in each layer with no signs of edema and with single cells of inflammation, respectively. The data of the histological processing were completely consistent with the results of morphometry: it was found out that in the experimental group, edema significantly decreased, the volume fraction of the pigment and macrophages decreased, and the volume fraction of the dermal fibers increased. The estimation of the inflammatory reaction was carried out according to the morphometric parameters of the volume fraction of inflammatory cells and had significant differences in all the experimental groups, decreasing in the following series: the negative control group> the comparison group> the experimental group> the group of intact animals (p <0.05).Conclusion. Based on the data obtained, the effectiveness of betamethasone in the treatment of local post-tattoo complications has been proved. In this case, the treatment of choice is the administration of this drug not traditionally subcutaneously, but using a tattoo machine that enables the targeted delivery of the substance to the area of the pathological process.Abbreviations: NC - negative control, VF - volume fraction